SOCIAL INFLUENCE CAN INCREASE PRO-ENVIRONMENTAL BEHAVIOR IN ECOTOURISM ENVIRONMENT: LITERATURE REVIEW - Andre Ludya Liap (Universitas Mercu Buana, 2022)
Abstract - Social influences that can increase a person's behavior change in acting for sustainable marketing of a tourist place, especially ecotourism, mangrove forests. This study seeks to reveal that overall, comparative social feedback may have a careful measure. That social behavior or human social behavior is controlled by some unconscious motives. Data collection for journal materials is carried out by studying literature, and preferably related to social influences, especially in pro-environmental behavior for ecotourism visits. Many developing countries are committed to ecotourism to receive economic growth through the use of natural resources. Positive social influence on purchase intention and multiple social identities are needed to understand how identity can lead to pro-environmental behavior and consumer judgments with pro-environmental variables, particularly in ecotourism places, mangrove forests can be suggested to explore processes of social influence and preference formation. , can form a person who lives socially. Obtained a new conceptual framework based on social theory. In the future, more in-depth research can be carried out to obtain a quantitative analysis of the effect of pro-environmental behavior variables as intervening variables or mediator variables on social influences in ecotourism site visits.